Primary Biliary Cirrhosis Beyond Ursodeoxycholic Acid - Corpechot, Christophe (Seminars in Liver Disease, 2016)
Although ursodeoxycholic acid remains the only approved pharmacotherapy for patients with primary biliary cirrhosis, the better characterization of factors responsible for the poor response to this drug and the emergence of several new putative therapeutic targets now offer significant opportunities to improve the management of patients and our capacity to treat them more efficiently. The availability of novel treatment options, such as fibrates, budesonide, and obeticholic acid, all capable of improving prognostic markers, invites us to reconsider our management and treatment strategies. Early identification of high-risk patients should remain a priority to deliver adjunctive therapies to appropriately selected populations and increase their chances of success. Given the absence of comparative trials, the choice between second-line treatments should be dictated by the biochemical, histological, and expected tolerance profiles. Here the author presents a brief overview of what should be known in this field and proposes a practical approach to facilitate decision making.
Keywords: budesonide; bezafibrate; fenofibrate; obeticholic acid; peroxisome proliferating-associated receptor; farnesoid X receptor; pregnane X receptor; fibroblast growth factor-19